Effect of seed dormancy on lipid accumulation and its molecular mechanism in oilseed rape - WANG Haoyi; LI Yuling; ZHU Le; JIANG Lixi (浙江大学学报. 农业与生命科学版)
Oilseed rape (Brassica napus L.) is one of the most widely grown oil crops and ranks the top-one edible oil in China. However, a significant proportion of the rapeseed oil in China relies on importation from abroad. In recent years, the planting area of oilseed rape in China continuously decreased and there was a paucity of cultivars which have wide adaption to adverse environment and resistance against a range of diseases. Above all, low seed oil content became a prominent problem. In order to improve rapeseed quality especially the seed oil content and change the passive situation of the country on international edible oil market, reinforcing the fundamental basic on the mechanism of seed oil formation seems necessary. In this review, we highlighted the influence of lipid decomposition during seed maturation on final seed oil content, and the phenomenon that seed oil rapidly decreases after reaching to a peak point about one week before harvest in rainy years. Some aspects, such as the metabolism of fatty acid in seeds, the acquisition of seed dormancy, and the association between post- peak seed oil decomposition and the acquisition of seed dormancy, were well illustrated to clarify the impact of seed dormancy on fatty acid accumulation. Finally, some constructive suggestions referring to the enhancement of rapeseed oil content in breeding practice were discussed.